2015
DOI: 10.1039/c4nj01764a
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer and fluorescence “turn-off” based CdTe quantum dots for vancomycin detection at nanogram level in aqueous serum media

Abstract: Mode of interaction of GSH-CdTe QDs with vancomycin and the mechanism of the fluorescence “turn-off” process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The slope of the curve increases with the increase in temperature, indicating that the quenching constant increases. All this evidence supports that the quenching mechanism for the interaction of BNCDs and curcumin is mainly initiated by a dynamic process and the IFE …”
Section: Resultssupporting
confidence: 77%
“…The slope of the curve increases with the increase in temperature, indicating that the quenching constant increases. All this evidence supports that the quenching mechanism for the interaction of BNCDs and curcumin is mainly initiated by a dynamic process and the IFE …”
Section: Resultssupporting
confidence: 77%
“…It was found that the IC 50 value was 13.74 ng/L, the IC 20 -IC 80 were 3.43-43.62 ng/L, and the IC 10 reached up to 1.07 ng/L according to the established IC-TRFIA for Van. The LOD value was 1.07 ng/L in the presented IC-TRFIA for Van, which is more sensitive (approximately 60-fold) compared with Kong et al (2017) established IC-ELISA for Van with LOD value of 0.06 ng/mL, and approximately 460-fold, 2.0 × 10 5 -fold and 2.5 × 10 5 -fold compare with Liang et al (2015), Sheng and Zhou (2017) and Usman and Hempel (2016) which were established fluorescence "turn-off" biosensor, two-dimensional liquid chromatography and HPLC for Van with LOD value of 0.46 ng/mL, 0.2 and 0.25 μg/mL respectively. In addition, it was slightly better than Liu, Yan, Hua, and Wang (2013), Hu et al (2018), Zhou et al (2015) and Sheng et al (2016) established IC-TRFIAs for thiacloprid, aflatoxin B 1 , chloramphenicol and diniconazole with LOD value of 1.9, 3.55, 8.0 and 21 ng/L, respectively.…”
Section: Ic-trfia Establishment Of Van and Its Analoguesmentioning
confidence: 80%
“…The absorption prole of the CdTe QDs also shows a broad range of UV-Vis light absorptivity . 67,68 The CdTe/NTU-9 nanocomposite offers synergistic improvements in overall light harvesting capability, as evidenced by its higher degree of energy absorption. The direct energy bandgap (E g ) values of the CdTe QDs, NTU-9, and CdTe/NTU-9 (calculated using Tauc's method) are estimated to be 2.40, 1.85, and 2.21 eV, respectively.…”
Section: Absorption Studiesmentioning
confidence: 99%